INSECTICIDAL EFFECTS OF ORANGE PEEL POWDER CONCENTRATION ON THE MANAGEMENT OF COWPEA BRUCHID Callosobruchus maculatus (Fabricius) (Coleoptera: Bruchidae) IN ALIERO, KEBBI STATE - Yusuf, I. J.; Mohammed, I. U.; Musa, A.; Muhammad, A.; Kwaifa, N. M.; Ibrahim, M.; Busari, Y.A.; Khadija, Z.U.; Afiu, A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
This study was conducted to evaluate the insecticidal effects of different concentrations of Orange Peel Powder on the management of Callosobruchus maculatus infestation on stored cowpea seeds in Aliero, Kebbi State. The experiment was carried out at the Insectary Unit of Molecular Biology Laboratory, Abdullahi Fodio University of Science and Technology, Aliero. The treatments consist of four (4) levels of Orange Peel Powder (2g, 4g, 6g, and 8g per 100g of cowpea seeds), (Permethrin 0.5 mg), and a control. These were arranged in a Completely Randomized Design (CRD) with three replications. Data were collected on Adult Mortality Rate, Number of Holed Seeds, Percentage Seed Damage, Seed Weight Loss, Larvae and Pupa Mortality Rate and Germination Percentage. Data collected were subjected to Analysis of Variance (ANOVA) and significant means were separated using Least Significance Difference (LSD) at (P<0.05%) probability level. The results revealed a significant (P<0.05%) differences among the treatments. The highest adult mortality (0.82%) was recorded by 8g of Orange Peel Powder, closely following the Permethrin (0.91%). Higher Orange Peel Powder levels also resulted in reduced seed damage, fewer holed seeds, lower weight loss, and higher larvae and pupa mortality rates compared to the control. Seed germination remained unaffected across treatments. The research concluded that, the Orange Peel Powder possesses an effective Insecticidal properties capable of suppressing C. maculatus in stored cowpea. The study recommends the use of higher concentrations particularly 8 g per 100 g of cowpea seeds for effective Bruchid control, along with continuous monitoring during storage.